Metabolic targeting of cancer by a ubiquinone uncompetitive inhibitor of mitochondrial complex I. Issue 3 (17th March 2022) - Jain, Shashi; Hu, Cheng; Kluza, Jerome; Ke, Wei; Tian, Guiyou; Giurgiu, Madalina; Bleilevens, Andreas; Campos, Alexandre Rosa; Charbono, Adriana; Stickeler, Elmar; Maurer, Jochen; Holinski-Feder, Elke; et al.
Summary: SMIP004-7 is a small molecule inhibitor of mitochondrial respiration with selective in vivo anti-cancer activity through an as-yet unknown molecular target. We demonstrate here that SMIP004-7 targets drug-resistant cancer cells with stem-like features by inhibiting mitochondrial respiration complex I (NADH:ubiquinone oxidoreductase, complex I [CI]). Instead of affecting the quinone-binding site targeted by most CI inhibitors, SMIP004-7 and its cytochrome P450-dependent activated metabolite(s) have an uncompetitive mechanism of inhibition involving a distinct N-terminal region of catalytic subunit NDUFS2 that leads to rapid disassembly of CI. SMIP004-7 and an improved chemical analog selectively engage NDUFS2 in vivo to inhibit the growth of triple-negative breast cancer transplants, a response mediated at least in part by boosting CD4 + and CD8 + T cell-mediated immune surveillance. Thus, SMIP004-7 defines an emerging class of ubiquinone uncompetitive CI inhibitors for cell autonomous and microenvironmental metabolic targeting of mitochondrial respiration in cancer. Graphical abstract: Highlights: SMIP004 compounds inhibit NADH:ubiquinone oxidoreductase (complex I) Unique ubiquinone uncompetitive mechanism of inhibition In vivo target engagement involves complex I subunit NDUFS2 Complex I inhibition reverses hypoxia and promotes cancer immune surveillance Abstract : Mitochondrial complex I is identified as the target of cancer selective cytotoxic agent SMIP004-7. Jain et al. show that anti-tumor activity involves ubiquinone uncompetitive inhibition of complex I, leading to a reversal of tumor hypoxia and promotion of tumor immune surveillance.